Pengaruh Penggunaan Alat Pelindung Diri (APD) Terhadap Keselamatan Dan Kesehatan Kerja Tenaga Medis Pada UPTD Puskesmas Afulu - Rafit Rahmat Daeli; Serniati Zebua; Martha Surya Dinata Mendrofa; Eduar Baene (Jurnal Ilmiah METANSI ”Manajemen dan Akuntansi”, 2024)
This study aims to determine whether there is influence of the use of personal protective equipment on the occupational safety and health of the medical personnel. This study use two variables, namely the use of PPE with Occupational safety and health at the Afulu Health Center UPTD, North Nias District. The type of research used in this research is descriptive with a quantitative approach, from the research findings it can be concluded that the use of personal protective equipment can explain occupational safety and health by 0,731 wuth a percenatage of 73,1% and remaining 26,9% being influenced by other variables that are not in the research. From the result of the T test calculation that T count>t table, namely 3,262>2,034 and the significant value is 0,003<0,05. So it can be said that the use of personal protective equipment has as positive and significant effect of on occupational safety and health.